Is Kinect Training Superior to Conventional Balance Training for Healthy Older Adults to Improve Postural Control? - Sápi, Mariann; Domján, Andrea; Fehérné Kiss, Anna; Pintér, Sándor (Games for health, 2019)
To investigate the effects of balance training to improve postural control in adults older than 60. Our aim was to find out if Kinect training is superior to the conventional balance training in aspects of functional balance tests and posturography measurements testing postural stability through visual feedback. Thirty subjects participated in the Kinect training group (29 women and 1 man), practiced Kinect Adventures and Sports, 23 volunteers (22 women and 1 man) attended the conventional balance training, and 22 participants (18 women and 4 men) were allocated to the no-intervention control group. Both interventions lasted for 6 weeks, three times a week, and 30 minutes per session. The Four-Square Step Test, Functional Reach Test, Timed Up and Go test, Timed Up and Go cognitive dual-task test were measured, and for the assessment of the limit of stability (LOS), we used computerized posturography. Measurements were taken before the training at baseline and 6 weeks after (follow-up) the interventions. Statistical analysis was done through two-factor mixed analysis of variance and Newman-Keuls post hoc test. Both training groups showed progress in the follow-up measurements; however, more statistically significant improvements were found in favor of the Kinect balance training group (Timed Up and Go test [P < 0.05], Timed Up and Go cognitive dual-task test [P < 0.05], Four-Square Step Test [P < 0.05], Functional Reach Test [P < 0.05], LOS movement velocity [P < 0.05]). Our results suggest that Kinect balance training may be a preferable and safe method for the healthy older adults to improve postural control and reduce the possibility of falling.